The effect of early childhood education and care services on the social integration of refugee families - Ludovica Gambaro; Guido Neidhöfer; Christa Katharina Spieß (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Devising appropriate policy measures for the integration of refugees is high on the agenda of many governments. This paper focuses on the social integration of families seeking asylum in Germany between 2013 and 2016. Exploiting regional differences in early childhood education and care (ECEC) services as an exogenous source of variation, and controlling for local level heterogeneity that could drive the results, we estimate the effect of ECEC attendance by refugee children on their parents' integration. We find a significant and substantial positive effect, in particular on the social integration of mothers. The size of the estimate is on average around 52% and is particularly strong for improved language proficiency and employment prospects.
Keywords: I26; J13; J15; 330; asylum seekers; refugees; childcare; early education; integration